No Place for Urban Art - Voutichtis, Christos; Rehm, Jonas Aaron (SAUC - Street Art and Urban Creativity (repository), 2016)
The following is an attempt to situate Urban Art within the philosophical tradition with and against Plato’s exclusion of the mimetic artist from the well-ordered city-state. It takes into account modern as well as postmodern literature on the concept of art and the city in order to rehabilitate a place for art within the city limits without sacrificing its potential to call into question any clear-cut limit the philosophical tradition has attempted to draw around the concepts of the subject, the work of art and the city itself.